Staged and non-staged anaerobic filters: performance in relation to physical and biological characteristics of microbial aggregates - Alves, M. M. (2000)
This work describes a comparative study of staged and non-staged anaerobic filters for treating a synthetic dairy waste. The effect of decreasing the hydraulic retention time from 2 days to 10 h at a constant substrate concentration of 9 g COD dm-3 by applying lateral feedings in the staged digester was evaluated with respect to overall reactor performance, in comparison with a conventional up-flow anaerobic filter. There was no advantage on the use of a multi-feed staged system under the operating conditions tested. The overall performance and the microbial activity segregation were similar for both configurations. The microbial aggregates present in both digesters, particularly in the top sections, changed significantly in biological, physical and morphological properties. The presence of aggregates larger than 4 mm equivalent diameter in those sections did not prevent a strong washout phenomenon. An effect of disintegration attributed to biogas accumulation and release was observed, when those large particles become smaller and their surface became rougher. Due to biomass accumulation, at the end of the trial period, only 40% of the total volume was occupied by the liquid phase.